An Initial Investigation of the Joint Classification of Hypomania- and Neurodevelopmental Disorder-Relevant Dimensions Within the Hierarchical Taxonomy of Psychopathology. (March 2023) - Stanton, Kasey; Khoo, Shereen; McDonnell, Christina G.; Villalongo Andino, Mara; Sturgeon, Taylor; Aasen, Laura
We examined hierarchical structural models of psychopathology in samples of (a) adults recruited online and screened based on psychopathology history ( N = 429) and (b) undergraduates ( N = 529) to inform classification of neurodevelopmental disorder (NDD)- and hypomania-relevant dimensions within the Hierarchical Taxonomy of Psychopathology (HiTOP). Results differed across samples in some ways, but converged to indicate that some NDD- and hypomania-relevant dimensions aligned closely with different HiTOP spectra. For example, some hypomania-relevant dimensions (e.g., affective lability) overlapped strongly with the internalizing spectrum, whereas others (e.g., self-perceived charisma) were reverse-indicators of detachment. Examination of cross-sectional and prospective correlates for emergent factors also was informative in some ways. This included NDD-relevant and disinhibited externalizing dimensions associating robustly with treatment seeking history and recent experiences of distress. These results provide initial insights into classifying NDD- and hypomania-relevant dimensions within the HiTOP and indicate a need for future research in this area.